Consumption of pediatric master formulas from a third level hospital of the social health security - Quispe, Susan V. (2024)
The aim of this study was to analyze the consumption of pediatric magistral formulas prepared in the pharmacotechnical area of the Alberto Sabogal Sologuren National Hospital during the period from April 2022 to June 2023. The research had a quantitative, descriptive, observational and cross-sectional approach. Data was collected from the EsSalud Servicios de Salud Inteligentes web portal; the sample analyzed was prescriptions for oral pediatric magistral formulations. The following criteria were considered: age, sex, diagnosis, pharmaceutical form, active ingredient, ATC (Anatomy Therapeutic Chemical) in an Excel 2016 data table and statistically analyzed with SPSS version 25. The results obtained from the research were: higher consumption of formulations in June and September (13.3%) of 2022; in March (21%) and June (19.2%) of 2023, in patients aged 0 to 29 days, male (51.9%) and female (48.4%); with the diagnosis of congenital malformations of the cardiac septa, in male (65.7%) and female (64.6%) patients. It is concluded that the consumption of oral pediatric magistral formulas had an increase of 3.2% during the analyzed period, with the papelillo formulation and in neonatal patients with congenital malformations of cardiac septum.